Rdzeniak – pierwotny nowotwór złośliwy ośrodkowego układu nerwowego u 18-letniego mężczyzny – opis przypadku = Medulloblastoma - primary malignant cancer of the central nervous system in an 18-year-old man – case report - Woźniak, Kamila; Ratuszek-Sadowska, Dorota; Nowacka, Agnieszka; Śniegocki, Maciej (Journal of Education, Health and Sport, 2016)
Woźniak Kamila, Ratuszek-Sadowska Dorota, Nowacka Agnieszka, Śniegocki Maciej. Rdzeniak – pierwotny nowotwór złośliwy ośrodkowego układu nerwowego u 18-letniego mężczyzny – opis przypadku = Medulloblastoma - primary malignant cancer of the central nervous system in an 18-year-old man – case report. Journal of Education, Health and Sport. 2016;6(8):695-700. eISSN 2391-8306. DOI http://dx.doi.org/10.5281/zenodo.61149 http://ojs.ukw.edu.pl/index.php/johs/article/view/3798 The journal has had 7 points in Ministry of Science and Higher Education parametric evaluation. Part B item 755 (23.12.2015). 755 Journal of Education, Health and Sport eISSN 2391-8306 7 © The Author (s) 2016; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 05.08.2016. Revised 25.08.2016. Accepted: 28.08.2016. Rdzeniak – pierwotny nowotwór złośliwy ośrodkowego układu nerwowego u 18-letniego mężczyzny – opis przypadku Medulloblastoma - primary malignant cancer of the central nervous system in an 18-year-old man – case report Kamila Woźniak1, Dorota Ratuszek-Sadowska2, Agnieszka Nowacka1, Maciej Śniegocki1 1. Klinika Neurochirurgii, Neurotraumatologii i Neurochirurgii Dziecięcej, Collegium Medicum im. Ludwika Rydygiera w Bydgoszczy, Uniwersytet Mikołaja Kopernika w Toruniu 2. Katedra i Klinika Rehabilitacji, Collegium Medicum im. Ludwika Rydygiera w Bydgoszczy, Uniwersytet Mikołaja Kopernika w Toruniu Streszczenie Rdzeniak (ang. medulloblastoma) to pierwotny nowotwór złośliwy ośrodkowego układu nerwowego, najczęściej rozwijający się w móżdżku. Należy do grupy prymitywnych guzów neuroektodermalnych (PNET). Rdzeniakowi przypisuje się najwyższy, IV° złośliwości histologicznej według WHO. Termin medulloblastoma wprowadzili w 1925 roku amerykańscy pionierzy neurochirurgii, Harvey Cushing i Percival Bailey. Rdzeniak jest najczęstszym nowotworem ośrodkowego układu nerwowego u dzieci. Autorzy przedstawiają opis przypadku klinicznego osiemnastolatka leczonego operacyjnie w Klinice Neurochirurgii, Neurotraumatologii i Neurochirurgii Dziecięcej Szpitala Uniwersyteckiego nr 1 im. dr A. Jurasza w Bydgoszczy z rozpoznanym w badaniu histopatologicznym rdzeniakiem. Słowa kluczowe: rdzeniak, medulloblastoma, pierwotny nowotwór złośliwy, neurochirurgia. Abstract Medulloblastoma is a primary cancer of the central nervous system, most often developing in the cerebellum. It belongs to a group of primitive neuroectodermal tumors (PNET). It assigns the highest, IV° histological according to the WHO. The term medulloblastoma introduced in 1925, the American pioneers of Neurosurgery, Harvey Cushing and Percival Bailey. Medulloblastoma is the most common cancer of the central nervous system in children. The authors present a case of clinical patient operating treated in the Department of Neurosurgery, Neurotraumatology and Pediatric Neurosurgery, Dr Antoni Jurasz University Hospital No.1 in Bydgoszcz histopathological diagnosed with medulloblastoma. Key words: medulloblastoma, primary malignant cancer, neurosurgery.